Crystallisation of the floating charge-need for adequate legislative direction in Nigeria (2013)
A floating charge is a present security on all or part of the assets of a company which hovers over them but gives the debtor the right to continue dealing with the assets until crystallisation. The process of the conversion from floating charge to its becoming fixed is known as crystallisation. This paper critically examines the current legal regime for crystallisation of the floating charge in Nigerian law. There is no framework on how crystallisation may be activated by the events stated in the Companies and Allied Matters Act 2004. The events listed in the law are grossly inadequate and does not take into consideration other events recognised under the common law and commercial practice. Preferential claims are not adequately protected under the current regime. The paper advocates for an urgent legislative intervention to properly define the floating charge and the regulation of crystallisation events to bring it to current international standards.